Stepping-up accurate quantification of chlorinated paraffins: Successful certification of the first matrix reference material - Ricci, Marina; de Boer, Jacob; Johansen, Jon Eigill; Liu, Huiling; Dumas, Pierre; Warner, Nicholas Alexander; Pērkons, Ingus; McGrath, Thomas Jacob; Røsrud Borgen, Anders; Bjørneby, Stine Marie; Tomasko, Jakub; Steer, Helena; et al. (Analytica chimica acta, 2024)
Chlorinated paraffins (CPs) are industrial chemicals categorised as persistent organic pollutants because of their toxicity, persistency and tendency to long-range transport, bioaccumulation and biomagnification. Despite having been the subject of environmental attention for decades, analytical methods for CPs still struggle reaching a sufficient degree of accuracy. Among the issues negatively impacting the quantification of CPs, the unavailability of well-characterised standards, both as pure substances and as matrix (certified) reference materials (CRMs), has played a major role. The focus of this study was to provide a matrix CRM as quality control tool to improve the comparability of CPs measurement results. We present the process of certification of ERM®-CE100, the first fish reference material assigned with certified values for the mass fraction of short-chain and medium-chain chlorinated paraffins (SCCPs and MCCPs, respectively). The certification was performed in accordance with ISO 17034:2016 and ISO Guide 35:2017, with the value assignment step carried out via an intercomparison of laboratories of demonstrated competence in CPs analysis and applying procedures based on different analytical principles. After confirmation of the homogeneity and stability of the CRM, two certified values were assigned for SCCPs, depending on the calibrants used: 31 ± 9 μg kg−1 and 23 ± 7 μg kg−1. The MCCPs certified value was established as 44 ± 17 μg kg−1. All assigned values are relative to wet weight in the CRM that was produced as a fish paste to enhance similarity to routine biota samples. The fish tissue ERM-CE100 is the first matrix CRM commercially available for the analysis of CPs, enabling analytical laboratories to improve the accuracy and the metrological traceability of their measurements. The certified CPs values are based on results obtained by both gas and liquid chromatography coupled with various mass spectrometric techniques, offering thus a broad validity to laboratories employing different analytical methods and equipment. [Display omitted] •Successful interlaboratory comparison for chlorinated paraffins (CPs) in fish.•First certification of a matrix reference material for short- and medium-chain CPs.•Certified values assigned combining LC and GC-based analytical results.•Fish CRM produced as a wet paste to enhance similarity to routine biota samples.